Characterization of volatile compounds and microstructure in different tissues of 'Eureka' lemon (Citrus limon). Issue 1 (31st December 2022) - Wang, Haiou; Xiao, HongWei; Wu, Yulong; Zhou, Feng; Hua, Chun; Ba, Long; Shamim, Sara; Zhang, Wei
ABSTRACT: Lemon fruits have a non-uniform histological structure, and are characterized by abundant volatile compounds. However, the distribution of volatile compounds in different tissues remain unknown. Herein, electronic nose (E-nose) and headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS) were employed to qualitatively and quantitatively analyze the volatile compound content in different tissues of fresh lemon fruits, while their microstructures were observed using several microscopy methods. The numbers of volatile compounds detected in the flavedo, albedo, juice vesicles, and segment wall were 41, 23, 29, and 19, respectively. The volatile compounds detected in the four tissues were mainly alkenes, alcohols, aldehydes, esters, and ketones, with a significant descending order in the total content ( p < .05). The measurements of E-nose and HS-SPME-GC-MS both showed that the highest total content of volatile compounds was in the flavedo, followed by albedo, juice vesicles, and segment wall ( p < .05). Furthermore, oil sacs and oil droplets were only observed in the flavedo by microstructure observation, where more essential oils (mainly volatile compounds) were distributed. The microstructure observation results also verified the measurement results of the E-nose and HS-SPME-GC-MS. These findings provide basic data for sensory evaluation and the comprehensive processing and utilization of lemon fruits.